ChemInform Abstract: Stark Sublevels in Tm3+—Yb3+ Codoped Na2Y2B2O7 Nanophosphor for Multifunctional Applications. Issue 29 (July 2015) - Soni, Abhishek Kumar; Dey, Riya; Rai, Vineet Kumar
Abstract Tm3+, Yb3+ co‐doped Na2Y2B2O7 with an average crystallite size of 18‐20 nm is prepared by solution combustion of a stoichiometric mixture of Y2O3, H3BO3, Na2CO3, Tm2O3, and Yb2O3 in conc.